2011
DOI: 10.1111/j.1474-9726.2010.00646.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related changes in mesenchymal stem cells derived from rhesus macaque bone marrow

Abstract: Summary The regeneration potential of mesenchymal stem cells (MSCs) diminishes with advanced age and this diminished potential is associated with changes in cellular functions. This study compared MSCs isolated from the bone marrow of rhesus monkeys (rBMSCs) in three age groups: young (< 5 years), middle (8–10 years), and old (> 12 years). The effects of aging on stem cell properties and indicators of stem cell fitness such as proliferation, differentiation, circadian rhythms, stress response proteins, miRNA e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
110
2
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(128 citation statements)
references
References 92 publications
(88 reference statements)
13
110
2
2
Order By: Relevance
“…Recently, studies showed that Rev-erba expression was increased, while Bmal1 expression was decreased in older BMSCs in vitro without the induction of circadian rhythm by dexamethasone exposure or serum shock [20,[29][30][31]. As a unit, the clock genes may regulate the aging process of cells in some way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, studies showed that Rev-erba expression was increased, while Bmal1 expression was decreased in older BMSCs in vitro without the induction of circadian rhythm by dexamethasone exposure or serum shock [20,[29][30][31]. As a unit, the clock genes may regulate the aging process of cells in some way.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with Rora, Rev-erba has a pivotal role in metabolism and was speculated to be the molecular junction for communicating clock gene signals to the metabolism [18,19]. Moreover, Yu et al found that the expression of Rev-erba in Rhesus macaques declines with age [20].…”
Section: Introductionmentioning
confidence: 99%
“…2D). The direct targets of miR-766 have not been identified, but its predicted targets are involved in pathways associated with cell survival after chemotherapy and aging (27,64). The deregulation of these miRNAs, along with others, indicate that the downregulation of cell cycle-related pathways is an important feature of infA infection.…”
Section: Figmentioning
confidence: 99%
“…When MSCs are cultured in vitro, 24-h oscillations in gene expression of core clock genes such as Bmal1 , Cry1 , Per2/3 , Rev-erbα/β , and Dbp are found, indicating that the peripheral circadian clock is present in these cells, independent of the presence of the central clock (Wu et al 2008 ). Differences in expression between MSCs of old and young animals are observed (Yu et al 2011 ). These rhythms seem to play an important role in physiology and pathophysiology.…”
Section: Circadian Clock Gene Expression In Adult Stem Cellsmentioning
confidence: 94%